Humor in the Novel “From Pesantren with Laugh” by Irvan Aqila: A Study of Humor - Irma Irma; Muhammad Ardi Kurniawan; Ida Puspita (JENTERA: Jurnal Kajian Sastra, 2026)
This study aims to describe the forms and types of humor in Irvan Aqila's novel From Pesantren with Laugh. Humor in literary works not only functions as entertainment but also as an aesthetic strategy to convey social reality in a light and communicative manner. This study uses a qualitative descriptive method with a literature study technique. Data in the form of narrative excerpts and dialogues containing humorous elements are explained through the stages of reduction, classification, and conclusion. The results of the study show that the humor in this novel is dominated by social humor, with as many as 25 data that appear through dialogues between characters in the form of light delivery, terminology twists, and reversals of meaning. In addition, 7 data of artistic humor were found in the form of literary humor manifested through the use of hyperbole, distorted metaphors, and exaggerated narrative descriptions. Meanwhile, behavioral humor, graphic humor, and personal humor were not found due to the limitations of the novel's medium, which plays an important role in building character traits, strengthening social relationships, and creating a humane and communicative atmosphere of Islamic boarding school life. These findings confirm that Arwah Setiawan's classification is relevant and applicable to analyzing humor in Indonesian literature. They also open up new academic space for the study of humor in Islamic boarding school-themed novels, which reflect the identity and socio-cultural dynamics of Indonesian Muslim youth. Abstrak Penelitian ini bertujuan untuk mendeskripsikan bentuk dan jenis humor dalam novel From Pesantren with Laugh karya Irvan Aqila. Humor dalam karya sastra tidak hanya berfungsi sebagai hiburan, tetapi juga sebagai strategi estetik untuk menyampaikan realitas sosial secara ringan dan komunikatif. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik studi pustaka. Data berupa kutipan narasi dan dialog yang mengandung unsur humor dianalisis melalui tahap reduksi, klasifikasi, dan penarikan simpulan. Hasil penelitian menunjukkan bahwa humor dalam novel ini didominasi oleh humor pergaulan, sebanyak 25 data yang muncul melalui dialog antartokoh berupa ejekan ringan, pemelesetan istilah, dan pembalikan makna. Selain itu, ditemukan 7 data humor kesenian dalam bentuk humor literatur yang diwujudkan melalui penggunaan hiperbola, metafora menyimpang, dan deskripsi naratif yang dilebih-lebihkan. Sementara itu, humor lakuan, humor grafis, dan humor personal tidak ditemukan karena keterbatasan medium novel tersebut berperan penting dalam membangun karakter tokoh, mempererat relasi sosial, serta menciptakan. suasana kehidupan pesantren yang humanis dan komunikatif. Temuan ini menegaskan bahwa klasifikasi Arwah Setiawan relevan dan dapat dipakai untuk menganalisis humor dalam karya sastra Indonesia. Temuan ini juga membuka ruang akademik baru untuk kajian humor pada novel berlatar pesantren yang mencerminkan identitas dan dinamika sosial-budaya remaja Muslim Indonesia.